2000
DOI: 10.1046/j.1440-1827.2000.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization classification of malignant lymphomas in Japan: Incidence of recently recognized entities

Abstract: New insights into the immunology and genetics of malignant lymphomas have allowed the recognition of new entities and the refinement of previously recognized disease categories. The relative incidence of these subtypes of malignant lymphoma is also known to differ according to geographic location. In order to clarify the current status of malignant lymphomas in Japan and the relative incidences of their subtypes, 3194 patients were classified according to the new World Health Organization (WHO) classification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…In a previous study in Japan the incidence rate of FL was 6.7% (Pathologists, 2000), but in a recent study in Japan they found a relatively high rate of FL (19%) similar to that of western countries (11-30%) (Aoki, et al, 2008). They suggest the following reasons for the relatively high rate of occurrence of follicular lymphomas.…”
Section: Histological Subtype Of Non-hodgkin's Lymphomamentioning
confidence: 83%
See 1 more Smart Citation
“…In a previous study in Japan the incidence rate of FL was 6.7% (Pathologists, 2000), but in a recent study in Japan they found a relatively high rate of FL (19%) similar to that of western countries (11-30%) (Aoki, et al, 2008). They suggest the following reasons for the relatively high rate of occurrence of follicular lymphomas.…”
Section: Histological Subtype Of Non-hodgkin's Lymphomamentioning
confidence: 83%
“…In an Indian study T-cell lymphomas formed 16.2% of the total NHL (Naresh, Srinivas, & Soman, 2000). Previous Japanese studies have reported a higher proportion of Tcell lymphoma, accounting for approximately 32-38% of non-Hodgkin lymphoma (Kadin, Berard, Nanba, & Wakasa, 1983;Pathologists, 2000), but the recent findings in Japan show the decreased frequency of T/NK cell lineage (25%) (Aoki, et al, 2008). In endemic area for HTLV1 in Japan, T/NK-cell neoplasm accounted for a higher percentage of lymphoid neoplasm, in Kyushu (30%) and Okinawa (38%), compared with other areas of Japan (18-20%) (Aoki, et al, 2008).…”
Section: Immunologic Characterization Of Non-hodgkin's Lymphomamentioning
confidence: 90%
“…PTCLs are a heterogeneous group of neoplasms accounting for 7–10% of NHL in the Western countries compared to 20–30% of NHL in East Asia, including China [5,11,12,13]. Patients often present with an advanced stage of the disease, and the neoplasms are characterized by widespread dissemination and aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have directly compared advanced stage DLBCL with PTCL, which is probably attributable to the rarity of PTCL as it accounts for only approximately 10% of all non-Hodgkin’s lymphomas (NHL) encountered in the Western countries [5,11] and about 25% of those in Asia [12,13]. Patients with PTCL with BMI were even fewer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) reveals extranodal involvements in more than 30% of patients at diagnosis [2,3]. The gastrointestinal tract, bone marrow, pancreas, liver, intravascular system, or brain is involved in patients with DLBCL.…”
Section: Introductionmentioning
confidence: 99%